Análise da substituição do chuveiro elétrico por aquecedor solar: uma contribuição ao setor elétrico na conservação de energia - Sáles, Isolda Cíntia Ferreira de (2008)
This thesis presents an analysis of the economic feasibility of replacing the shower when electric heaters by solar in a unifamiliar residence in the city of Maceio/AL. The solar heating systems, plain plate type and with natural movement (for siphon term) are very suitable for heating household water. In Brazil, due to its climatic conditions are very favorable for these types of systems, they are widely used especially in the Northeast since they depend on sunlight and solar radiation received locally. It is presented a brief introduction describing the entire methodology used for the completion of project. Are given the variables of interest, the design and assembly of the system are. The given practical application of the methodology used is presented in a case study conducted in a unifamiliar residence at the Maceió/AL city. With all mounted system can assess the efficiency of the project, its economic viability and economy generated over 20 years. The outcomes obtained they showed what the substitution of the bath electric for heating solar is viable, generates an economy about to the consumer of low income of R$ 1.826,05, about to the of average income of R$ 4.290,01 & high-yielding of R$ 5.919,75 durante the 20 years of I screen.